A method of ileostomy closure associated with a low anastomotic leak rate: does operative time matter? - Karam, Charbel; Meagher, Alan P. (International Surgery Journal, 2022)
Background: Anastomotic leaks (AL) are serious post-operative complications associated with a high morbidity following routine ileostomy closure. Studies comparing standard methods of closure show no difference in outcome. The benefit of longer operative time has not been investigated. Methods: Baseline characteristics and surgery outcomes for all patients who had an ileostomy closure from 1994-2015 at a single centre by a single surgeon were extracted from medical records. An electronic literature search of EMBASE, PubMed was performed to identify systematic reviews of Randomised controlled trials (RCT) reporting pooled leak rates and operative time for stapled vs hand sutured anastomosis. A meta-analysis using data from 4 eligible RCT was used to compare outcomes between the new versus standard techniques. Results: A total of 415 patients underwent ileostomy closure during the study period with no leaks (0%, 95%CI 0-0.9); compared with 10 leaks reported in 649 patients (1.5%, 95%CI 7-28) from four trials. This risk difference of 1.55% corresponds to a Number needed to treat (NNT) of 66. Two individual trials reported leak rates of 2-3% which were statistically significantly different to the case series leak rate (p<0.05). Mean operative time was 170 minutes (95%CI 163-177) (p<0.05) using the modified functional end-end anastomosis and stapled: 67 minutes (95%CI 59-74) and hand-sutured: 80 minutes (95%CI 70-90). Conclusions: The increased operative time performing our modified stapled functional end-end anastomosis is associated with a very low leak rate compared with stapled or hand-sutured anastomosis.